Strontium ranelate stimulates the activity of bone-specific alkaline phosphatase: interaction with Zn ²⁺ and Mg ²⁺ - Fernández, Juan Manuel (2014)
Strontium ranelate (SR) is an orally administered and bone-targeting anti-osteoporotic agent that increases osteoblast-mediated bone formation while decreasing osteoclastic bone resorption, and thus reduces the risk of vertebral and femoral bone fractures in postmenopausal women with osteoporosis. Osteoblastic alkaline phosphatase (ALP) is a key enzyme involved in the process of bone formation and osteoid mineralization. In this study we investigated the direct effect of strontium (SR and SrCl₂) on the activity of ALP obtained from UMR106 osteosarcoma cells, as well as its possible interactions with the divalent cations Zn²⁺ and Mg²⁺. In the presence of Mg²⁺, both SR and SrCl₂ (0.05–0.5 mM) significantly increased ALP activity (15–66 % above basal), and this was dose-dependent in the case of SR. The stimulatory effect of strontium disappeared in the absence of Mg²⁺. The cofactor Zn²⁺ also increased ALP activity (an effect that reached a plateau at 2 mM), and co-incubation of 2 mM Zn²⁺ with 0.05–0.5 mM SR showed an additive effect on ALP activity stimulation. SR induced a dose-dependent decrease in the Km of ALP (and thus an increase in affinity for its substrate) with a maximal effect at 0.1 mM. Co-incubation with 2 mM Zn²⁺ further decreased Km in all cases. These direct effects of SR on osteoblastic ALP activity could be indicating an alternative mechanism by which this compound may regulate bone matrix mineralization.